Implementasi Metode Bagdadi bagi Peningkatan Kualitas Baca Al-Qur’an di Pondok Pesantren Daarusshofwah - Nazli Arfah Nasution; Ina Salmah Febriani (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2023)
ABSTRACT Indonesia is known as the country with the largest Muslim population in the world. The release of the World Population Review (WPR) in 2020 outlines that the total population of Indonesia is 273.500.000. Of this amount, the percentage of Muslims amounted to 87.2 percent or the equivalent of 229 million people. This number is certainly encouraging as well as being the main challenge in the ability to read Al-Quran. The chairman of the Indonesian Al-Quran Foundation, Komjen Pol Dr (HC) Syafruddin, as quoted from republika.co.id said that as many as 65 percent of the Indonesian population who are Muslims cannot read Al-Quran. This data refers to in-depth studies and research by Islamic youth organizations and Islamic youth leaders. Several Islamic youth organizations and youth leaders conducted in-depth research on the ability to read the Al-Quran among Indonesian Muslims. As a result, it was found that only 35 percent or around 80 million Muslim population in Indonesia can read the Al-Quran. The rest, 65 percent or about 149 million Muslim population cannot read the Al-Quran. Based on the facts above, the Baghdadi method as a method of reading Al-Quran is the answer. The method that was born in the era before the 1980s and then refined by the Central Leadership of Jam'iyyatul Qurra wal Huffadz Nahdlatul Ulama (PP-JQHNU) has been introduced and studied throughout Indonesia. Not much different from several other methods such as the Yanbu'a, Ummi, al-Barqi, Qiraati, Ottoman, Jibril, and Iqra' methods, this method focuses on improving the quality of reading the Al-Quran. Both the Baghdadi method and some of the methods of reading the Al-Quran mentioned above aim to make Muslims not only recognize letters but are able to read letters according to the makharijul huruf (the place where the letters come out) and the shifatul huruf (the characteristics of the Hijaiyyah letters). This study uses a qualitative approach with the object of study at the Daarus Sofwah Islamic Boarding School, Bogor which has implemented the Bagdadi method to improve the quality of reading the Al-Quran for students. It was found that the Bagdadi method was able to be a way for students to enjoy studying and reading the Al-Quran although there were some who found this method difficult. The teacher's role is very decisive in success of this method for increasing quality of reading Al-Quran.